The ADALINE neuron modification for solving the problem on searching for the reusable functions of the information system - Muhamed, Saif Q.; Mohammed, Mohammed Q.; Evlanov, Maksym; Kliuchko, Halyna (Eastern-European Journal of Enterprise Technologies, 2018)
The problem of reducing costs in developing information systems and software products was considered. It was proposed to replace the IT project staff in a number of repeatable processes and the works connected with development of software products by intelligent information technologies provided that such a replacement is economically viable. It was proposed to use the apparatus of artificial neural nets as a tool for creation of such technologies. Among the main directions of automation of the information system development processes, there is the problem of searching for reusable functions to implement the functional requirement to the system. To solve this problem, it was suggested to modify the formal description and block diagram of the ADALINE neuron. The essence of this modification is the use of frame networks for formal description of reusable functions and functional requirements to the information system. Comparison of these formal descriptions makes it possible to identify a reusable function that, to the extent possible, corresponds to the functional requirement to the IS. Solution of the search problem results in a formal description of the functional requirement to the system. This description is formed on the basis of formal descriptions of the function found and the functional requirement. Proceeding from this representation of the search problem, a special algorithm of training the modified neuron was developed. Its essence consists in finding the maximum similarity of the formal description of the functional requirement to the system among the descriptions of reusable functions. Proceeding from the results of modification of the elements, block diagram of the ADALINE neuron was modified. The approach was proposed and the main features of architectural solutions for implementation of the modified block diagram were considered.